2002
DOI: 10.1590/s0036-46652002000500010
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of computerized tomography (CT) findings in central nervous system (CNS) infection due to Cryptococcus neoformans var. gattii in immunocompetent children

Abstract: Cranial CT scans of eleven immunocompetent children with central nervous system (CNS) infection due to Cryptococcus neoformans var. gattii were retrospectively reviewed. These children had an average age of 8.8 years and positive culture for C. n. var. gattii in cerebrospinal fluid. The most common signs and symptoms were headache, fever, nuchal rigidity, nausea and vomiting. No normal cranial CT was detected in any patient. Hypodense nodules were observed in all patients. The remaining scan abnormalities were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 12 publications
1
10
0
5
Order By: Relevance
“…In the State of Pará, it an infantile cryptococcal meningitis frequency of 18.6% was verified for 43 cases diagnosed from 2003 to 2007 6 and 24.3% in 78 cases diagnosed from 1992 to 1998 in the same state 3 . A frequency of 33% of cases in children was observed in the State of Amazonas 7 and 21% in the State of Piaui 8 .…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the State of Pará, it an infantile cryptococcal meningitis frequency of 18.6% was verified for 43 cases diagnosed from 2003 to 2007 6 and 24.3% in 78 cases diagnosed from 1992 to 1998 in the same state 3 . A frequency of 33% of cases in children was observed in the State of Amazonas 7 and 21% in the State of Piaui 8 .…”
Section: Introductionmentioning
confidence: 87%
“…In a study of tomographic alterations in 11 children with meningitis by C. gattii in the State of Pará, Brazil, all cases presented hypodense nodules, most of them located in the basal ganglia 6 . The same study also described hydrocephalus and diffuse cortical atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, symptoms of headache, fever nuchal rigidity, nausea, and vomiting were common (219,221,256). Cranial CT scans of 11 children with CNS disease revealed hypodense nodules in all patients, cerebral atrophy in 9, hydrocephalus in 6, and hydrocephalus with cerebral atrophy in 5 (220). Meningoencephalitis is also characteristic of most pediatric cases in PNG (218).…”
Section: Clinical Manifestations In Childrenmentioning
confidence: 96%
“…In contrast, concurrent pulmonary and cerebral cryptococcomas and hydrocephalus were more frequently associated with C. gattii independent of host status (27,29). Correa et al reported hypodense nodules on cerebral CT scans, often in the basal ganglia, in all 11 immunocompetent children studied (220). Obstructive hydrocephalus has been described in 17 to 50% of C. gattii infections (27-29, 130, 251).…”
Section: Neurological Infection (I) Computerized Tomographymentioning
confidence: 99%
“…PAULA et al 69 in a study of the cryptococcosis agent, in 40 cases not associated to infection by HIV, demonstrated the proportion of gattii of about 33% while in AIDS patients this rate is below 1% 51,58,62 . CORREA et al 22 have observed alterations, through tomographical images, in 11 immunocompetent children with infection of the central nervous system (CNS) by gattii variety. In a study carried out in Rio de Janeiro City, patients with AIDS exposed to spores of C. neoformans species in a home environment have presented a risk to cryptococcosis two times more than non-exposed AIDS patients 66 .…”
mentioning
confidence: 99%